2019
DOI: 10.1016/j.arthro.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Open Posterior Shoulder Stabilization—When Is It Needed? Glenoid Bone Loss Patterns Are Not Created Equal

Abstract: Posterior shoulder instability remains a poorly understood pathologic entity. Our current treatment algorithm of simple posterior shoulder instability is fairly straightforward, with most patients receiving arthroscopic capsulorrhaphy with labral repair. However, in those with a failed arthroscopic intervention and/or with bony pathology, the optimal treatment is much less clear. As we move forward to evaluate how to optimally treat these patients, it will be critical to better understand the bony pathologies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Some authors suggest open capsulorrhaphy should be used following the failure of an arthroscopic procedure or when patients have no obvious labral detachment or when patients have associated inferior instability suggesting excessive capsular laxity. 15,16 In a more recent meta-analysis of open and arthroscopic stabilization for PSI, DeLong et al demonstrated a trend toward more favorable results following arthroscopic techniques for recurrence rate (8% vs. 19%), subjective stability (91% vs. 80%), patient satisfaction (94% vs. 86%), return to sport at any level (92% vs. 66%), and return to the previous level of play (67% vs. 37%). 6 However, to optimize outcomes in patients presenting with PSI, it is imperative that additional prospective studies be performed to better understand which patient and injury characteristics may benefit more from open rather than arthroscopic stabilization, such as age, activity level, sports played, and various soft tissue and boney abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest open capsulorrhaphy should be used following the failure of an arthroscopic procedure or when patients have no obvious labral detachment or when patients have associated inferior instability suggesting excessive capsular laxity. 15,16 In a more recent meta-analysis of open and arthroscopic stabilization for PSI, DeLong et al demonstrated a trend toward more favorable results following arthroscopic techniques for recurrence rate (8% vs. 19%), subjective stability (91% vs. 80%), patient satisfaction (94% vs. 86%), return to sport at any level (92% vs. 66%), and return to the previous level of play (67% vs. 37%). 6 However, to optimize outcomes in patients presenting with PSI, it is imperative that additional prospective studies be performed to better understand which patient and injury characteristics may benefit more from open rather than arthroscopic stabilization, such as age, activity level, sports played, and various soft tissue and boney abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The mean proportion of males was 80% based on five studies. 15,16,[19][20][21] Mean follow-up was between 1 and 10.8 years based on six studies (9 years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] 6,10,15,16,20,21 All nine studies used the posterior open wedge technique. Seven studies used an autograft derived from the iliac crest, 10,15,16,[18][19][20][21] two from the acromion, 19,21 two from the scapular spine, 6,18 and one study did not report the autograft source.…”
Section: Study Characteristicsmentioning
confidence: 99%
“… 1 Posterior instability accounts for approximately 2–10% of shoulder instability cases and can manifest itself on a spectrum, ranging from mild subluxation to frank dislocation. 2 6 Causation is often multifactorial including, glenoid retroversion, trauma, posterior labral tears, hyperlaxity and poor neuromuscular control. 7 9 Due to the wide spectrum of clinical manifestations and aetiologies, it can be challenging to determine appropriate indications for treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Furthermore, the challenges in evaluation of posterior instability likely underlies the challenges in treating this challenging pathology, with mixed results in open and arthroscopic treatments. 4 , 6 , 7 , 8 , 14 , 18 , 19 …”
mentioning
confidence: 99%